2015
DOI: 10.1017/s1380203815000094
|View full text |Cite
|
Sign up to set email alerts
|

From football stadium to Iron Age hillfort. Creating a taxonomy of Wessex hillfort communities

Abstract: The variability of Wessex hillfort form, use and development has long been noted, but not satisfactorily explained. This paper seeks to explain this variability and suggests that each hillfort may have had its own distinctive history of use, dependent upon the nature of the hillfort community -the people who visited, inhabited and used the hillfort. This paper starts by using grid-group analysis to define identities that can be found among modern communities -such as that of spectators of contemporary professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…On one side are those who consider hillforts to be the elite residences of tribal leaders and central places of social, economic, political, and religious systems (Cunliffe, 1984b; Karl, 2011; Driver, 2013). On the other side are those who regard hillfort societies as very communal in emphasis and ideology, lacking marked social distinctions (Collis, 1981; Sharples, 1991a, 2010; Hill, 1996; Lock, 2011; Davis, 2015). In an important contribution, J.D.…”
Section: The Early and Middle Iron Age In Wessex Southern Britainmentioning
confidence: 99%
See 1 more Smart Citation
“…On one side are those who consider hillforts to be the elite residences of tribal leaders and central places of social, economic, political, and religious systems (Cunliffe, 1984b; Karl, 2011; Driver, 2013). On the other side are those who regard hillfort societies as very communal in emphasis and ideology, lacking marked social distinctions (Collis, 1981; Sharples, 1991a, 2010; Hill, 1996; Lock, 2011; Davis, 2015). In an important contribution, J.D.…”
Section: The Early and Middle Iron Age In Wessex Southern Britainmentioning
confidence: 99%
“…This position, in Britain at least, has been extensively critiqued in recent years. Boundary construction, for instance, has been interpreted as a largely symbolic act defining the relationship between the communities involved (see especially Sharples, 2010), whilst I, amongst others, have highlighted that the internal layouts of many British hillforts appear to emphasize social conformity rather than promote social differences (Davis, 2015). In this sense, hillforts in Britain have come to be interpreted as an expression of the prestige of a community rather than of an individual (Collis, 2010; Sharples, 2010; Lock, 2011; Davis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The issue is not the number of excavations, but rather it is a problem with the scale and nature of those excavations. Only two large-scale research excavations have been undertaken in the region in the last 50 years – at Caerau Hillfort (Davis & Sharples 2014; 2015) and Llanmaes (Lodwick & Gwilt 2007) – but both are still ongoing and neither is yet fully published. The vast majority of other recent excavations have been evaluations undertaken in advance of development.…”
Section: The Settlement Evidencementioning
confidence: 99%
“…It is likely that Castle Ditches, Llantwit Major can also be added to this group as a significant amount of the interior may have been lost to coastal erosion (Whittle 1992). The only site to have been excavated on an extensive scale is Caerau Hillfort (Davis & Sharples 2014; 2015). This has demonstrated that the hillfort was probably constructed in the Early Iron Age ( c. 500 BC ) and was intensively occupied, possibly until the 1st century BC .
Fig.
…”
Section: The Settlement Evidencementioning
confidence: 99%
See 1 more Smart Citation